2014
DOI: 10.3389/fimmu.2014.00297
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal SIV Vaccines Comprising Inactivated Virus Particles and Bacterial Adjuvants Induce CD8+ T-Regulatory Cells that Suppress SIV-Positive CD4+ T-Cell Activation and Prevent SIV Infection in the Macaque Model

Abstract: A new paradigm of mucosal vaccination against human immunodeficiency virus (HIV) infection has been investigated in the macaque model. A vaccine consisting of inactivated simian immunodeficiency virus (SIV)mac239 particles together with a living bacterial adjuvant (either the Calmette and Guerin bacillus, Lactobacillus plantarum or Lactobacillus rhamnosus) was administered to macaques via the vaginal or oral/intragastric route. In contrast to all established human and veterinary vaccines, these three vaccine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 65 publications
1
31
0
Order By: Relevance
“…Rhesus monkeys as a model for prion disease allowed circadian rhythm parameters to be monitored, which is not possible in human CJD cases. In parallel we proved transmission of BSE and human vCJD prions to a non-human primate species (Asante et al, 2015). This comprehensive project was funded by the EU and headed by John Collinge and Adriano Aguzzi working in London and Zurich, respectively.…”
Section: Research Activitiesmentioning
confidence: 81%
See 1 more Smart Citation
“…Rhesus monkeys as a model for prion disease allowed circadian rhythm parameters to be monitored, which is not possible in human CJD cases. In parallel we proved transmission of BSE and human vCJD prions to a non-human primate species (Asante et al, 2015). This comprehensive project was funded by the EU and headed by John Collinge and Adriano Aguzzi working in London and Zurich, respectively.…”
Section: Research Activitiesmentioning
confidence: 81%
“…Unfortunately, none of the cumbersome vaccine trails was successful, although partial contributions to protection could be assessed. Even in 2014, rhesus and cynomolgus monkeys served as animal models in innovative vaccination strategies like the elimination of proviral DNA (Andrieu et al, 2014).…”
Section: Research Activitiesmentioning
confidence: 99%
“…Importantly, in their paper, Lu et al showed that the group of four Chinese RMs vaccinated with iSIV only had a clear anti-SIV antibody response (IgM and IgG); moreover, Chinese RMs vaccinated with iSIV-L. plantarum had a strong suppressive activity generated by major histocompatibility complex E (MHC-E)-restricted regulatory and/or suppressive CD8 ϩ T cells. These cells were measurable only in fresh cells (12,28) and were not evaluated in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…However, in contrast to all established human and veterinary vaccines, none of the protected macaques developed anti-SIV antibodies [25]. …”
Section: The Bacillus Of Calmette and Guerin A Tolerogenic Adjuvant mentioning
confidence: 99%
“…Four RMs were vaccinated intragastrically with iSIV and LR; two control RMs received LR only, and two iSIV received only [25]. …”
Section: Absence Of Immune Reactivity Of Indian Macaques To Intra-gasmentioning
confidence: 99%